ANALISIS REPRESENTASI BENTUK EKSPRESI FILM TILIK SUTRADARA AGUNG WAHYU PRASETYO - Surya Darma; Sri Wahyuni; Muhammad Ali Mursid Alfathoni (Smart Education, 2025)
Abstract: The purpose of this study is to analyze the representation of the form of expression in the film Tilik (2018) by director Wahyu Agung Prasetyo. The reason the researcher analyzed the film Tilik (2018) is because it authentically visualizes the social dynamics of rural communities, especially in Java, through dialogue and visuals of its characters. This research method uses descriptive qualitative research with content analysis techniques in the film Tilik (2018) through scenes, visuals, dialogue, narration, facial expressions, body language, and cinematography techniques used. The results of this study produce three main forms of expression in the film Tilik (2018), namely emotional expressions seen through facial expressions and gestures that depict several forms of expression such as anger, happiness, sadness, disgust, and surprise, then linguistic expressions in the form of depiction through sarcastic dialogue and satire through gossip practices as a model of social forms, and visual expressions depicted through cinematography techniques such as close-ups, narrow framing, and natural lighting as supporters of emotional assertiveness. The conclusion of this study is that the film Tilik (2018) presents a micro-portrait of rural Javanese society, which faces complex and dynamic problems.Â Keywords: Tilik (2018), forms of expression, analysis of expression, cinematography Abstrak: Tujuan penelitian ini adalah analisis representasi bentuk ekspresi film Tilik (2018) karya sutradara Wahyu Agung Prasetyo. Alsan peneliti menganalisis film Tilik (2018) ini karena memvisualkan dinamika sosial masyarakat di pedesaan khususnya Jawa secara autentik melalui dialog dan visual tokohnya. Metode penelitian ini menggunakan penelitian kualitatif desktiptif dengan teknik menganalisis isi (content analysis) pada film Tilik (2018) melalui adegan, visual, dialog, narasi, ekpresi wajah, bahasa tubuh, dan teknik sinematografi yang digunakan. Hasil penelitian ini menghasilkan tiga bentuk ekspresi utama pada film Tilik (2018), yaitu ekspresi emosional yang terlihat melalui mimik wajah dan gestur yang menggambarkan beberapa bentuk ekspresi seperti marah, bahagia, kesedihan, rasa muak, dan terkejut, selanjutnya ekspresi linguistik bentuk penggambarannya melalui dialog sarkastik dan bentuk sindiran melalui praktik gosip sebagai model dari bentuk sosial, dan ekspresi visual yang di gambarkan melalui model teknik sinematografi seperti close-up, framing sempit, dan pencahayaan alami sebagai pendukung ketegasan dari emosional. Kesimpulan dari penelitian ini adalah film Tilik (2018) menghadirkan potret mikro masyarakat di pedesaan Jawa yang memiliki permasalahan kompleks, dan dinamis.Â Kata kunci: Film Tilik (2018), bentuk ekspresi, analisis ekspresi, sinematografi